CD5+B lymphocytes are the main source of antibodies reactive with non-parasite antigens in Trypanosoma congolense infected cattle - Buza, J.J.; Sileghem, M.R.; Gwakisa, P.S.; Naessens, Jan (1997)
Mice infected with African trypanosomes produce exceptionally large amounts of serum IgM, a major part of which binds to non-trypanosome antigens such as trinitrophenol and single-strand DNA. In this paper, we describe that in cattle infected with Trypanosoma congolense and T. vivax, similar antibodies are found, although they bind mainly to protein antigens, such as Beta-galactosidase, ovalbumin and ferritin. The parasite non-specific IgM antibodies appear around the same time as the parasite-specific antibodies, but their origin and function are not clear. We tested the hypothesis that CD5+ B cells (or B-1 cells), which increase during trypanosome infections in cattle, are responsible for production of antibodies to non-trypanosome antigens. Splenic CD5+ and CD5- B cells from infected cattle were sorted and tested in a single cell blot assay. The numbers of immunoglobulin-secreting cells were similar in both B-cell populations. However, antibodies with reactivity for non-trypanosome antigens were significantly more prevalent in the CD5+ B-cell fraction and were exclusively IgM. The preference for production of these antibodies by CD5+ B cells and the expansion of this subpopulation during infections in cattle, strongly suggest that CD5+ B cells are the main source of trypanosome non-specific antibodies. We propose that these antibodies are natural, polyreactive antibodies that are predominantly secreted by CD5+ B cells. Since B-1 cells are up-regulated in many states of immune insufficiency, the immunosuppression associated with trypanosome infections may be responsible for the increase of this subset and the concomitant increase in trypanosome non-specific antibodies.